Reflections about the conception of body and movement for an integral education in the early childhood - Elizabeth Gutiérrez; Johanna Andrea Castillo (Corporación Universitaria Minuto de Dios, 2014)
This article proposes to educators at the initial or pre-school level a reflection about an ideal about how the child should be construed in terms of its physical and psychosocial being during its development. This study is based on neurophysiologic studies on human development on which all the educational proposals rest and on the teaching experiences which experiences that have sought revitalize kindergarten schooling around the exploration of the body, understanding movement and motor activity as educational, creative, expressive elements and from the point of view of consciousness, emotions and relationships. Based on these foundations, the article discusses how corporeality and active experience through movement could be included in the education of early childhood in a classroom context as it influences the development of the child and as well as assessing its responses to the stimuli provided.